The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1124/jpet.111.179762
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rab1 GTPase and Endoplasmic Reticulum-to-Golgi Trafficking Underlies Statin's Toxicity in Rat Skeletal Myofibers

Abstract: HMG-CoA reductase inhibitor statins are used for the treatment of hypercholesterolemia. However, statins have adverse effects on skeletal muscles with unknown mechanism. We have reported previously that fluvastatin induced vacuolation and cell death in rat skeletal myofibers by depleting geranylgeranylpyrophosphate (GGPP) and suppressing small GTPases, particularly Rab (FASEB J 21:4087-4094, 2007). Rab1 is one of the most susceptible Rab isoforms to GGPP depletion and is essential for endoplasmic reticulum (ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 42 publications
7
37
0
Order By: Relevance
“…One group using rat immortalized L6 myoblasts reported that the depletion of FPP is critical for myotoxicity (22), but another laboratory using the same cell line suggested that GGPP was the critical isoprenoid (12). In our hands, it was not FPP (3 mM), but GGPP (3 mM) alone, because the addition of GGPP, not FPP, in the presence of fluvastatin completely canceled the toxic effects of statins in skeletal myofibers (15,17). FPP also failed to rescue myotoxicity in a study using myotubes differentiated from C2C12 myoblasts (23).…”
Section: Depletion Of Geranylgeranylpyrophosphate Triggers Statin Myomentioning
confidence: 79%
See 4 more Smart Citations
“…One group using rat immortalized L6 myoblasts reported that the depletion of FPP is critical for myotoxicity (22), but another laboratory using the same cell line suggested that GGPP was the critical isoprenoid (12). In our hands, it was not FPP (3 mM), but GGPP (3 mM) alone, because the addition of GGPP, not FPP, in the presence of fluvastatin completely canceled the toxic effects of statins in skeletal myofibers (15,17). FPP also failed to rescue myotoxicity in a study using myotubes differentiated from C2C12 myoblasts (23).…”
Section: Depletion Of Geranylgeranylpyrophosphate Triggers Statin Myomentioning
confidence: 79%
“…We focused on Rab1, which was responsible for the traffic from the ER to the Golgi apparatus because this is the origin and the bottle-neck pathway for all the vesicle traffic systems. Application of 1 mM fluvastatin reduced the membrane-bound form of Rab1, and GGPP supplementation canceled the reduction of membrane-bound Rab1 as well as vacuolation and cell death (17). This directly indicates that fluvastatin treatment inactivated Rab1.…”
Section: Inactivation Of Rab Gtpases Reproduced Statin Myotoxicity Inmentioning
confidence: 85%
See 3 more Smart Citations